AUTONOMIC DYSFUNCTION IN COVID-19 PATIENTS - Jamil, Hassan; Jamil, Javairia; Nadir, Bakhtawar; Ibrahim, Mohammad; Hai, Abdul (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Post-COVID-19 syndrome is a poorly understood aspect of the covid pandemic, with clinical features that overlap with symptoms of autonomic/small fiber dysfunction. An analysis of autonomic dysfunction following COVID-19 was lacking. Various studies have reported and encountered patients with debilitating symptoms following viral infections who were subsequently found to have orthostatic intolerance syndromes. Orthostatic intolerance syndromes include orthostatic hypotension (OH), vasovagal syncope (VVS) and postural orthostatic tachycardia syndrome (POTS). The pathophysiology hinges on an abnormal autonomic response to orthostasis (standing up). It was also observed that a strong association between post-COVID-19 fatigue and anxiety existed. This is of particular note. Here, we audit and conducted a review of the studies and patients with confirmed history of COVID-19 infection that presented or were referred for autonomic testing for symptoms concerning for para or postinfectious autonomic dysfunction.